Evaluation of biofilm formation on acrylic resins used to fabricate dental temporary restorations with the use of 3D printing technology - Justyna Mazurek-Popczyk; Adam Nowicki; Katarzyna Arkusz; Łukasz Pałka; Anna Zimoch-Korzycka; Katarzyna Baldy-Chudzik (BMC, 2022)
Abstract Background Temporary implant-retained restorations are required to support function and esthetics of the masticatory system until the final restoration is completed and delivered. Acrylic resins are commonly used in prosthetic dentistry and lately they have been used in three-dimensional (3D) printing technology. Since this technology it is fairly new, the number of studies on their susceptibility to microbial adhesion is low. Restorations placed even for a short period of time may become the reservoir for microorganisms that may affect the peri-implant tissues and trigger inflammation endangering further procedures. The aim of the study was to test the biofilm formation on acrylamide resins used to fabricate temporary restorations in 3D printing technology and to assess if the post-processing impacts microbial adhesion. Methods Disk-shaped samples were manufactured using the 3D printing technique from three commercially available UV-curable resins consisting of acrylate and methacrylate oligomers with various time and inhibitors of polymerization (NextDent MFH bleach, NextDent 3D Plus, MazicD Temp). The tested samples were raw, polished and glazed. The ability to create biofilm by oral streptococci (S. mutans, S. sanguinis, S. oralis, S. mitis) was tested, as well as species with higher pathogenic potential: Staphylococcus aureus, Staphylococcus epidermidis and Candida albicans. The roughness of the materials was measured by an atomic force microscope. Biofilm formation was assessed after 72 h of incubation by crystal violet staining with absorbance measurement, quantification of viable microorganisms, and imaging with a scanning electron microscope (SEM). Results Each tested species formed the biofilm on the samples of all three resins. Post-production processing resulted in reduced roughness parameters and biofilm abundance. Polishing and glazing reduced roughness parameters significantly in the NextDent resin group, while glazing alone caused significant surface smoothing in Mazic Temp. A thin layer of microbial biofilm covered glazed resin surfaces with a small number of microorganisms for all tested strains except S. oralis and S. epidermidis, while raw and polished surfaces were covered with a dense biofilm, rich in microorganisms. Conclusions UV-curing acrylic resins used for fabricating temporary restorations in the 3D technology are the interim solution, but are susceptible to adhesion and biofilm formation by oral streptococci, staphylococci and Candida. Post-processing and particularly glazing process significantly reduce bacterial biofilm formation and the risk of failure of final restoration.